Pengaruh Solvabilitas terhadap Harga Saham pada PT. Japfa Comfeed Indonesia Tbk - Bahri, Syamsul; Amalia, Rasya Rizky; Suhartono, Suhartono (www.bsi.ac.id, 2023)
The stock exchange as a source of corporate funding in competing globally to increase company profits and in general improve people's welfare, plays a very important role in the nation's economy. The research aims to determine the effect of solvency on stock prices at PT. Japfa Comfeed Indonesia Tbk. The research method uses interval ratio data and secondary data from financial report data for the 2015-2021 period. Data collection techniques use time series data. The results show that the variable debt to equity ratio has no significant effect and has the opposite direction, which means that an increase in the debt to equity ratio will reduce stock prices. Because investors think that the DER implemented by PT. Japfa Comfeed Indonesia Tbk. has an impact on increasing prices and resulting in lower investor purchasing decisions.Keywords: Solvability, Share Price, PT. Japfa Comfeed Tbk